DEVELOPING ISLAMIC-BASED READING MATERIALS IN GENRE-BASED CONTEXT FOR THE EIGHTH GRADERS OF MTsN MODEL KOTA JAMBI - Dewi Syafitri (Universitas Jambi, 2019)
The purpose of this study was to find out whether the developing Islamic-based reading materials in genre-based context were valid, practical and had potential effect for the eighth graders of MTsN Model Kota Jambi. Developmental research proposed by Akker (1999) i.e analysis, design, evaluation and revision was applied in this study. In the evaluation phase, formative evaluation model proposed by Tessmer (1993) was used (i.e self evaluation, expert review, one to one, small group and field test). There were 3 students participating in one to one evaluation, 9 students in small group and one class (34 students) in field test. There were also two validators in reviewing the Islamic-based reading materials in genre-based context. One was expert of content and another one was expert of instructional design. The result of experts judgment showed that the product was valid with average score was 89.2 categorized in good validity. The product was practical with average score in one to one evaluation was 84.3 and in small group phase was 86.8. The potential effect of the product could be seen from the average score of students’ achievement in field test. The score was 92.8 meaning that the score was higher than the criterion of minimal mastery (KKM) of English subject in MTsN Model Kota Jambi (75). Therefore, the product had potential effect categorized in very good level.